2007
DOI: 10.1007/s10620-006-9292-0
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Markers of Bone Metabolism in Children with Helicobacter pylori Infection

Abstract: We investigated the biochemical markers of bone metabolism in children with Helicobacter pylori infection. Biochemical markers of bone metabolism and serum levels of vitamin B12, ferritin and estradiol were measured in 41 H. pylori-positive (+) children (23 girls, 18 boys; aged 11.8+/-3 years). Serum levels of intact parathyroid hormone, ss-collagen I carboxy terminal telopeptide, total alkaline phosphatase (ALP), bone-specific ALP, N-terminal cross-links of human procollagen type I, N-mid-osteocalcin, calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 50 publications
(55 reference statements)
1
23
0
Order By: Relevance
“…Similar to the findings of a study in children that found that H. pylori infection was not accompanied by significant changes in circulating estradiol, parathyroid hormone, cross-linked collagen I carboxy terminal telopeptide, bonespecific alkaline phosphatase, N-terminal cross-links of human pro-collagen type I, N-mid-osteocalcin, calcium, and phosphate [8], we did not find significant differences in bone turnover markers between IgG H. pylori positive and IgG H. pylori negative postmenopausal women.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Similar to the findings of a study in children that found that H. pylori infection was not accompanied by significant changes in circulating estradiol, parathyroid hormone, cross-linked collagen I carboxy terminal telopeptide, bonespecific alkaline phosphatase, N-terminal cross-links of human pro-collagen type I, N-mid-osteocalcin, calcium, and phosphate [8], we did not find significant differences in bone turnover markers between IgG H. pylori positive and IgG H. pylori negative postmenopausal women.…”
Section: Discussionsupporting
confidence: 87%
“…This proinflammatory response and the release of inflammatory cytokines in H. pylori infection may indicate a plausible role for this organism in bone resorption. However, only 4 studies in the medical literature investigated H. pylori infection in relation to bone health, all of which reported contradictory findings [8][9][10][11]. In contrast to a case-control study that reported a higher prevalence of CagA-positive strains in osteoporotic men, two studies with small samples of women showed that H. pylori infection with or without chronic atrophic gastritis in postmenopausal women [11] and H. pylori associated gastritis in women [10] were not associated with decreased BMD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations